1984
DOI: 10.3382/ps.0632007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Phosphorus Level and Source on Productive Performance and Egg Quality of Two Commercial Strains of Laying Hens

Abstract: An experiment was conducted to study the influence of dietary total phosphorus (TP) level and source on the performance of two strains of commercial layers for two consecutive production years (26 to 68 and 76 to 116 weeks of age, respectively). Diet 1 contained .4% TP; Diets 2, 3 and 4 contained .5, .6, and .7% TP with supplemental P from dicalcium phosphate (DCP); Diets 5 and 6 contained .5 and .6% TP, respectively, with supplemental P from a sample of raw rock phosphate (RRP-1); Diets 7 and 8 contained .5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
9
1
1
Order By: Relevance
“…Only two studies by Said et al (1984) and Snow et al (2004) fed different phosphorus levels throughout the second cycle and reported requirement of 0.3 and more than 2 g/kg of diet respectively. Said et al (1984) and Snow et al (2004) have used general linear model and treatment mean differences for determination of AP requirement. In the current study, AP requirement was evaluated using the recently developed method (Robbins et al, 2006) and approaches and various nonlinear models were fitted to the data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two studies by Said et al (1984) and Snow et al (2004) fed different phosphorus levels throughout the second cycle and reported requirement of 0.3 and more than 2 g/kg of diet respectively. Said et al (1984) and Snow et al (2004) have used general linear model and treatment mean differences for determination of AP requirement. In the current study, AP requirement was evaluated using the recently developed method (Robbins et al, 2006) and approaches and various nonlinear models were fitted to the data.…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer studies have investigated AP requirement of molted laying hens (Holder, 1981;Said et al, 1984;Bar et al, 2002 andSnow et al, 2004). Only two studies by Said et al (1984) and Snow et al (2004) fed different phosphorus levels throughout the second cycle and reported requirement of 0.3 and more than 2 g/kg of diet respectively. Said et al (1984) and Snow et al (2004) have used general linear model and treatment mean differences for determination of AP requirement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations